2013
DOI: 10.1111/cmi.12141
|View full text |Cite|
|
Sign up to set email alerts
|

p53 signalling controls cell cycle arrest and caspase-independent apoptosis in macrophages infected with pathogenicLeptospiraspecies

Abstract: SummaryPathogenic Leptospira species, the causative agents of leptospirosis, have been shown to induce macrophage apoptosis through caspaseindependent, mitochondrion-related apoptosis inducing factor (AIF) and endonuclease G (EndoG), but the signalling pathway leading to AIF/EndoGbased macrophage apoptosis remains unknown. Here we show that infection of Leptospira interrogans caused a rapid increase in reactive oxygen species (ROS), DNA damage, and intranuclear foci of 53BP1 and phosphorylation of H2AX (two DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 72 publications
5
62
0
1
Order By: Relevance
“…It is well known that the protein p53, encoded by the TP53 gene, has a crucial role in multi-cellular organisms, where it regulates apoptosis and the cell cycle (15). When a cell is exposed to damage, p53 is activated and inhibits various downstream target genes involved in apoptosis and cell cycle arrest, including bax, p53-upregulated modulator of apoptosis (PUMA), bcl-2 and p21 (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the protein p53, encoded by the TP53 gene, has a crucial role in multi-cellular organisms, where it regulates apoptosis and the cell cycle (15). When a cell is exposed to damage, p53 is activated and inhibits various downstream target genes involved in apoptosis and cell cycle arrest, including bax, p53-upregulated modulator of apoptosis (PUMA), bcl-2 and p21 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Wildtype pCMV-Tag2C-transfected THP-1 cells and normal THP-1 cells without transfection were used as controls. Besides, the THP-1 cells for chpK or mazF gene transfection were pretreated with 100 mM of the pan-caspase inhibitor Z-VAD-FMK (Sigma) and then detected by flow cytometry as above to distinguish necrosis from caspase-dependent apoptosis [37].…”
Section: Measurement Of Cell Death Caused By Leptospiral Proteinsmentioning
confidence: 99%
“…Mononuclear macrophages and neutrophils have been shown to phagocytose leptospires, but only the former can kill the phagocytosed intracellular leptospires [11, 12], indicating that mononuclear macrophages are much more important than neutrophils in the defense mechanisms against leptospiral infection. Our previous study showed that L .…”
Section: Introductionmentioning
confidence: 99%